Agriculture in Southeast Asia: Rethinking contemporary issues using sociology of gender and family - Veronica L. Gregorio (Universitas Trunojoyo Madura, 2021)
This article provides an overview of how agricultural development and structural changes affects women in Southeast Asia. By employing critical literature review, it enumerates how global agriculture can be characterized as under a modern capitalist system of production by looking at trends on labor and distress migration, scientific and technological innovations (STIs), and intensification of non-traditional agricultural exports (NTAEs). Following this, it makes a case for Southeast Asia’s ASEAN4 (Philippines, Thailand, Indonesia, Malaysia) explaining how the conditions of women farmers should be explored further, not just in a developmental lens but in sociology of gender and family approaches. The article then discusses regional works about masculinization and feminization, engendered resistance, agency and multiplicity of identities, and intra-household relations. Towards the conclusion, it emphasizes points on challenging the terms “farmer” and “feminization,” reconsidering regional contexts, examining the family’s intra-household relationship, scrutinizing the position of the local state, and ways to move forward.